Remuneration and Work Environment Analysis on Job Satisfaction and Performance of Soldiers Kri Bung Tomo-357 - Pradipta Putra, Nicodemus; Pintor Siolemba, Shine; Fauzi, Achmad (Journal of World Science, 2023)
In creating a conducive work environment, there is a complete division of labor down to the lowest soldier or officer so that everyone consciously knows what their duties are and who is responsible for the results of their work. On the Warship of the Republic of Indonesia Tomo – 357, there was a problem with the behavior of the soldiers who were often late for gatherings. There are still soldiers who do not leave work on time. The quality of the work produced is not optimal so it does not achieve the expected goals. This study aims to determine the effect of soldier remuneration and the work environment that creates job satisfaction on soldier performance on KRI Tomo-357. This study uses a type of quantitative research. All KRI Bung Tomo-357 soldiers with the rank of Officers, Non-commissioned Officers and Privates totaled 85 people. The data analysis method in this study uses Partial Least Square (PLS) with the help of Smart PLS 3.0 Software. Based on the results of the study, it shows that remuneration influences job satisfaction. Work environment contributes to job satisfaction. Remuneration contributes to job performance. The work environment contributes to the soldier's performance. Job satisfaction contributes to soldier performance. The Influence of the Work Environment on Soldier Performance through Soldier Satisfaction, the indirect effect is smaller than the direct effect of the Work Environment on Soldier Performance, meaning that the Work Environment on Soldier Performance has a greater direct influence.